Skeletal maturity and physical capacity in 14-year-old Icelandic soccer players - Sigurður Skúlil Benediktsson 1991- (2022)
The objective of this study was to examine the association of skeletal maturity with physical capacity in 14-year-old Icelandic soccer players. Peak height velocity (PHV) and physical capacity were examined. Furthermore, the association between skeletal maturity and PHV measurements was examined. Data were collected from (n = 48) 14-year-old soccer players. Players were from two local clubs in Reykjavík, Iceland. Skeletal maturity was measured with a gold standard left-wrist x-ray. Peak height velocity (PHV) was also assessed. Various measurements were performed such as maximum oxygen uptake (VO2max), 40 m sprint test, countermovement jump (CMJ), standing long jump (SLJ), and a Yo-Yo Intermittent recovery test (Yo-Yo IR1). Basic anthropometry was assessed with height and weight. Players also answered a soccer practice questionnaire. Statistical analysis was performed using t-test and Pearson's correlation coefficient analysis. Results from the correlation coefficient showed that skeletal maturity was associated with sprint performance (r = -0.564, r = -0.573, p < 0.001), jump performance (r = 0.380, p < 0.007) and (r = 0.353, p < 0.014), but not with aerobic endurance tests. The PHV measurements showed statistical difference between mid- PHV and post- PHV groups in 40 m sprint test (p < 0.026) and both aerobic endurance test, VO2max (mL·kg-1·min-1) (p < 0.017) and the Yo-Yo IR1 test (p < 0.011). There was no association between skeletal maturity and PHV measurements. These results suggest that soccer players with increased biological maturity perform better in speed and power attributes. The results determine the expected maturity developmental effect on physical performance and different bone development in 14-year-old soccer players in Iceland. Markmið þessarar rannsóknar var að kanna fylgni beinþroska og afkastagetu á meðal 14 ára íslenskra drengja í knattspyrnu og kanna hámarks vaxtarhröðun leikmanna (e. peak height velocity) í samanburði við afkastagetu. Fylgni beinþroska og hámarks ...